Simultaneous versus Sequential Bilateral Cataract Surgery for Infants with Congenital Cataracts: Visual Outcomes and Economic Costs - Dave, Hreem (Arch Ophthalmol, 2010)
OBJECTIVES: To compare the incidence of adverse events, visual outcomes and economic costs of sequential versus simultaneous bilateral cataract surgery for infants with congenital cataracts. METHODS: We retrospectively reviewed the incidence of adverse events, visual outcomes and medical payments associated with simultaneous versus sequential bilateral cataract surgery for infants with congenital cataracts who underwent cataract surgery when 6 months of age or younger at our institution. RESULTS: Records were available for 10 children who underwent sequential surgery at a mean age of 49 days for the first eye and 17 children who underwent simultaneous surgery at a mean age of 68 days (p=.25). We found a similar incidence of adverse events between the two treatment groups. Intraoperative or postoperative complications occurred in 14 eyes. The most common postoperative complication was glaucoma. No eyes developed endophthalmitis. The mean absolute interocular difference in logMAR visual acuities between the two treatment groups was 0.47±0.76 for the sequential group and 0.44±0.40 for the simultaneous group (p=.92). Hospital, drugs, supplies and professional payments were on average 21.9% lower per patient in the simultaneous group. CONCLUSIONS: Simultaneous bilateral cataract surgery for infants with congenital cataracts was associated with a 21.9% reduction in medical payments and no discernible difference in the incidence of adverse events or visual outcome.